(untitled) (Eurasian Journal of Philology Science and Education, 2025)
In the context of multiculturalism and globalization, teaching literature in higher education institutions faces the challenge of integrating a cultural approach. This article examines the effectiveness of the cultural approach to teaching Russian-language literature in universities in Kazakhstan, with particular attention to the relationship between the text and its cultural context. The aim of the study is to experimentally test the effectiveness of the cultural approach to teaching literature, taking into account the cultural context. The study analyzes the impact of the proposed methodology on students’ cultural literacy, the development of their analytical skills, and their ability to interpret literary texts in their historical and cultural perspectives. The scientific significance of the work lies in the development of a new methodology for teaching literature based on a cultural approach, while its practical significance lies in the development of recommendations for educators implementing this approach in the educational process. The research methodology included comparative analysis, textual study of literary works, surveys, and student testing. The results of the study demonstrated that the use of the cultural approach increased student engagement, improved their understanding of the text, and contributed to the development of intercultural communication skills. Particular attention is paid to the analysis of the relationship between the literary text and its cultural context. The study utilizes works by authors such as A.S. Pushkin, F.M. Dostoevsky, V.V. Nabokov, and L.E. Ulitskaya, which serve as a basis for exploring cultural codes and historical realities reflected in their writings. The experimental group showed a 20.6% improvement in test results compared to the control group. This study confirms the importance of integrating the cultural approach for modernizing educational programs in multinational countries. Keywords: cultural approach, text and context, teaching in universities, digital technologies, interactive teaching methods.